Advances in Emerging Photonic Memristive and Memristive‐Like Devices. Issue 28 (9th August 2022) - Wang, Wenxiao; Gao, Song; Wang, Yaqi; Li, Yang; Yue, Wenjing; Niu, Hongsen; Yin, Feifei; Guo, Yunjian; Shen, Guozhen
Abstract: Possessing the merits of high efficiency, low consumption, and versatility, emerging photonic memristive and memristive‐like devices exhibit an attractive future in constructing novel neuromorphic computing and miniaturized bionic electronic system. Recently, the potential of various emerging materials and structures for photonic memristive and memristive‐like devices has attracted tremendous research efforts, generating various novel theories, mechanisms, and applications. Limited by the ambiguity of the mechanism and the reliability of the material, the development and commercialization of such devices are still rare and in their infancy. Therefore, a detailed and systematic review of photonic memristive and memristive‐like devices is needed to further promote its development. In this review, the resistive switching mechanisms of photonic memristive and memristive‐like devices are first elaborated. Then, a systematic investigation of the active materials, which induce a pivotal influence in the overall performance of photonic memristive and memristive‐like devices, is highlighted and evaluated in various indicators. Finally, the recent advanced applications are summarized and discussed. In a word, it is believed that this review provides an extensive impact on many fields of photonic memristive and memristive‐like devices, and lay a foundation for academic research and commercial applications. Abstract : With the unique characteristic, photonic memristive and memristive‐like devices significantly facilitate the construction of neuromorphic computing and artificial visual systems. This review elaborates on the resistive switching mechanisms, active layer materials, and potential applications in the scientific and industrial of photonic memristive and memristive‐like devices, aiming to provide a systematic and comprehensive insight into its development.